ANALISIS TINGKAT KEPUASAN PELANGGAN TERHADAP KUALITAS PELAYANAN BUS RAPID TRANSIT,SURABAYA (Studi Kasus: Pelayanan Suroboyo Bus) - Royyan Firdaus; Atik Wahyuni; Julistyana Tistogondo (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2021)
Suroboyo Bus is a type of bus based on Bus Rapid Transit. This public transportation is a new transportation issued by the Surabaya City Government with various routes in the middle of the City. The newly opened route is the MERR-Gunung Anyar route. Therefore, the study was conducted to determine the assessment of customers on the service quality of Suroboyo Bus. In this study, the independent variable uses the SERVQUAL (Service Quality) method which has five important dimensions, namely Tangible (X1), Assurance (X2), Reliability (X3), Responsiveness (X4), and Empathy (X5). While the dependent variable is the quality of service infrastructure (Y). The number of samples is 100 respondents using multiple linear regression analysis and a method of importance performance analysis (IPA). The five independent variables have a significant effect on the dependent variable simultaneously and there are several independent variables that have partial influence. Based on the research results, the performance of the services provided has not met the expectations of customers / passengers. But the customer feels that the services provided are quite satisfying. As well as there are several infrastructures that must be prioritized for repair, namely the addition of shelter buildings along withinfrastructure, and the responsiveness of officers in order to increase the level of customer satisfaction and service quality.